IMPACT OF COVID-19 ON STUDENT LEARNING OUTCOMES AT SDIT ALFARABI TANJUNG SELAMAT - Nila Lestari; Khairina Ulfa Syaimi (Sensei International Journal of Education and Linguistic, 2021)
This research is based on the occurrence of the COVID-19 pandemic. The purpose of this study is to determine the impact of COVID-19 on student learning outcomes of SDIT Al Farabi Tanjung Selamat. This type of research is qualitative research using descriptive qualitative analysis techniques. Subjects in this study were all students of SDIT Al-Farabi. The object of this research is to look at the impact of COVID-19 on student learning outcomes during the COVID-19 Pandemic. Referring to the results of observations, interviews and documentation and identification of student learning outcomes from the Even Semester / Academic Year 2019/2020) is higher than the student learning outcomes during the COVID-19 Pandemic (Odd Semester / Academic Year 2020/2021. concluded that the COVID-19 pandemic has greatly affected the world of education, one of which is that the learning outcomes of SDIT Al Farabi Tanjung Selamat SDIT students have decreased compared to the period before the COVID-19 Pandemic.